Liquid biopsy for brain tumors. (3rd October 2017) - Shankar, Ganesh M.; Balaj, Leonora; Stott, Shannon L.; Nahed, Brian; Carter, Bob S.
ABSTRACT: Introduction : Minimally invasive methods will augment the clinical approach for establishing the diagnosis or monitoring treatment response of central nervous system tumors. Liquid biopsy by blood or cerebrospinal fluid sampling holds promise in this regard. Areas covered : In this literature review, the authors highlight recent studies describing the analysis of circulating tumor cells, cell free nucleic acids, and extracellular vesicles as strategies to accomplish liquid biopsy in glioblastoma and metastatic tumors. The authors then discuss the continued efforts to improve signal detection, standardize the liquid biopsy handling and preparation, develop platforms for clinical application, and establish a role for liquid biopsies in personalized medicine. Expert commentary : As the technologies used to analyze these biomarkers continue to evolve, we propose that there is a future potential to precisely diagnose and monitor treatment response with liquid biopsies.